Social and pedagogical conditions for increasing the role of the family in increasing the physical activity of school-age children - Pukhov D.N.; Tsareva A.V.; Grebennikov A.I.; Malinin A.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the socio-pedagogical components of family influence on the level of physical activity of school-age children. Methods and structure of the study. A survey was conducted of 2555 schoolchildren aged 11-16 years (1287 boys and 1268 girls), during which schoolchildren answered questions related to their physical activity and characteristics of family life. Results and conclusions. The survey results showed that in families where its members engage in physical exercise and sports, there are relationships of cooperation, mutual assistance and support, family members spend a lot of time communicating and interacting together, children grow up with a conscious attitude towards physical activity, they are involved in physical activities culture and sports, they feel protected.